Correlations between the Surface Topography and Mechanical Properties of Friction Stir Welds - Roman Hartl; Fabian Vieltorf; Michael F. Zaeh (Metals, 2020)
Friction stir welding is a modern pressure welding process, which is particularly suitable for aluminum alloys. Several studies have been conducted to investigate the interrelations between the process parameters, such as the welding speed and the tool rotational speed, and the resulting mechanical properties of the joint. This study explored the connections between the surface topography of the welds, such as the flash height and the seam underfill, and their mechanical properties (ultimate tensile strength; elongation at break; and Vickers hardness). For this purpose, a total of 54 welding experiments at three different welding speeds were conducted using the aluminum alloy EN AW-6082-T6. The welded specimens were examined using visual inspection, topographic analysis, metallography, hardness measurements, and uniaxial tensile tests. Afterward, a statistical analysis was performed in order to determine the correlation coefficients between the surface topography and the mechanical properties of the welds. The strongest correlations were between the surface topography and the ultimate tensile strength. Thereby, the most pronounced relations were found between the seam underfill as well as the arc texture formation of the weld and its ultimate tensile strength. The interrelations between the surface topography and the elongation at break, as well as the hardness of the welds, were less pronounced. The higher the welding speed became, the less pronounced the interrelations were. The results show the potential of a non-destructive monitoring system based on the topography to support the prediction of the acceptability of welded parts.